Analysis of the selectivity filter of the voltage-gated sodium channel Na(v)Rh - Zhang, Xu (Nature Publishing Group, 2013)
NaChBac is a bacterial voltage-gated sodium (Na(v)) channel that shows sequence similarity to voltage-gated calcium channels. To understand the ion-permeation mechanism of Na(v) channels, we combined molecular dynamics simulation, structural biology and electrophysiological approaches to investigate the recently determined structure of Na(v)Rh, a marine bacterial NaChBac ortholog. Two Na(+) binding sites are identified in the selectivity filter (SF) in our simulations: The extracellular Na(+) ion first approaches site 1 constituted by the side groups of Ser181 and Glu183, and then spontaneously arrives at the energetically more favorable site 2 formed by the carbonyl oxygens of Leu179 and Thr178. In contrast, Ca(2+) ions are prone to being trapped by Glu183 at site 1, which then blocks the entrance of both Na(+) and Ca(2+) to the vestibule of the SF. In addition, Na(+) permeates through the selective filter in an asymmetrical manner, a feature that resembles that of the mammalian Na(v) orthologs. The study reported here provides insights into the mechanism of ion selectivity on Na(+) over Ca(2+) in mammalian Na(v) channels.